Quality Control Using the SPC Method to Reduce Defective Products in Finished Garments At VYO Factory Convection - Puspita, Della Ayu (KH. A. Wahab Hasbullah University, 2024)
CV.Vyo Factory, which is located at Kebakkramat, Karanganyar, Solo, is a manufacturing industry that operates in the convection industry. The problem raised in this research is the increase in defects in the production produced. As a result, companies continue to produce products that are defective in production. The results of initial observations in the field showed that there were many defective products from production at CV. Vyo Factory. It can be seen that the number of damaged products from February 2023-February 2024 continues to increase. The method used in this research is the Statistical Process Control method, attribute data and variable data collection is carried out at CV. Vyo Factory was obtained by observing the population of t-shirt products that experienced defects at the time of the research from 01 May 2024 to 30 June 2024. This is based on a control chart calculation graph (c-chart), which shows that defective t-shirt products exceed control limits, so improvements or evaluation of quality control need to be carried out. Based on the results of the analysis, it is known that using a Check Sheet, it can be seen that there are 3 categories of product damage, namely material defects, stitching defects and finishing defects, with the number of each material defect being 48 pcs, stitching defects being 275 pcs and finishing defects being 7 pcs. fruit. fruit. With a total of 330 damaged products produced, the monthly average is 1.68%.